Skin Biopsy in Glycogenosis Type III - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
Electron microscopy of skin specimens of five patients with glycogenosis type III were correlated with clinical, biochemical, and electrophysiological findings from the Divisions of Neuropathology and Neuropediatrics, Ciudad Sanitaria Valle de Hebron, Barcelona, Spain.